How to Improve Environment Performance? The Comparison of Stakeholder Perceptions on How to Improve Air Quality in China - Liu, Hehe (Frontiers in Environmental Science, 2022)
The air quality and carbon neutrality strategies in China has attracted the growing concern of multiple stakeholders. Through face-to-face surveys conducted in five major cities in North China, we compared the stakeholders’ perceptions. Our research reveals conflicting perceptions among stakeholders. On the one hand, local authorities and academics prefer to focus on market-based regulation to prevent air pollution. Enterprise managers, however, do not want to be regulated. On the other hand, social groups expect more information about air pollution to be released, but local authorities do not see releasing that information as a top priority. These differences of perceptions can actually be useful in terms of policymaking.